Modeling of sound propagation in urban streets containing trees using Markovian technique - Haron, Zaiton (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2009)
It is claimed that the trees may become a possible control method for noise in streets and hence contribute another step towards a sustainable environment. This paper examined the capability of an abatement scheme containing absorbent facades and trees in streets through a simulation model developed using the novel approach based upon Markovian techniques. The study showed that sound pressure level in a street containing trees relative to that in an empty street predicted by the Markov model was in good agreement with predictions obtained using commercial software, RAYNOISE model. Within the scope and assumptions in this study, it is shown streets containing trees and absorbent building façade result in sound reductions typically less than 1.5 dB. Hence trees in streets appear to have only a slight effect on sound attenuation, and thus make no significant contribution towards producing a sustainable environment in this respect.